Spatial variation of organochlorine pesticides and dissolved organic matter in urban closed lakes. Issue 4 (2nd April 2020) - Popa, Cristina L.; Dontu, Simona I.; Levei, Erika A.; Ioja, Cristian I.; Popa, Ana-Maria; Miclean, Mirela; Hoaghia, Maria-Alexandra; Cadar, Oana; Carstea, Elfrida M.
Abstract: Closed lakes located in urban parks act as sinks of organochlorine pesticides (OCPs), which have been used, for decades, as insecticides, herbicides and fungicides. The closed lakes from Bucharest, Romania, are periodically managed to prevent eutrophication and accumulation of pollutants. However, it is not known if these practices reduce or enhance the legacy pollution with OCPs. The aim of this study was to explore the spatial variation of OCPs in closed lakes. The total concentration of OCPs in water and sediments ranged between 0.0176 and 37.1 µg/L, and between 122 to 1, 890 ng/g, respectively. The concentrations of OCPs were compared with the consensus-based sediment quality guidelines (SQGs) in order to evaluate the ecological risks of sediments. The highest potential adverse effects were associated with γ-HCH exposure. Periodical draining and dredging of lakes lead to the resuspension of contaminants, increasing pesticide bioavailability and accumulation in sediments. In addition, we observed that fluorescent dissolved organic matter (DOM) might influence the OCPs cycle. The quantity and character of fluorescent DOM can provide further insight into OCPs degradation. Also, this study may help urban planners to determine the state of urban waters and to find the best solution for water management.